INFLUENCE OF INSTRUCTION LEADERSHIP STYLE, TASK DISCIPLINE, DUTY COMMITMENT TO THE PERFORMANCE OF POLICE PERSONNEL AT THE DIRECTORATE OF COMMUNITY DEVELOPMENT OF POLDA KEPRI - Rudi Syahriadi Idris; Rizki Firmanda; Hendri Herman (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This research aims to find out the influence of instructional leadership style, task discipline, duty commitment to personnel performance. The object of this research is the police at the directorate of community development of the kepri regional police. The population in the study was 86 respondents. The sample calculation used the slovin formula, so the number of samples in this study was as many as 46 respondents. Research data is obtained by spreading questionnaires to respondents to then be tabulated and processed using spss data processing applications. From the results of the study, it is known that the instruction leadership style has an insignificant effect on personnel performance, task discipline has a significant effect on personnel performance, and duty commitment has an insignificant effect on personnel performance, as well as instructional leadership style, task discipline, and duty commitment simultaneously have a significant effect on personnel performance. Adjusted R Square is 39.2%. This meant that instructional leadership style, task discipline and duty commitment were able to explain personnel performance by 39.2%, while the remaining 60.8% was explained by other variables not included in the study